Method for improving efficiency of solar cell by brominated polycyclic thiophene
Patent Information
- Application Number
- CN202411760905.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The hole transport layer materials in existing perovskite solar cells have problems such as poor thermal stability, high cost and low hole mobility, which affects the battery efficiency and stability.
The orientation and π-π stacking degree of P3HT are modified by adding a specific brominated polycyclothiophene additive to the poly(3-hexylthiophene-2,5-diyl) (P3HT) solution, thereby improving charge transfer and extraction of the hole transport layer.
The photoelectric conversion efficiency of perovskite solar cells has been improved from 14.70% to 16.16%, 16.36% and 16.88%, while improving the performance and thermal stability of the device, promoting the commercialization process of perovskite solar cells.
Smart Images

Figure CN119630252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell preparation, and in particular to a method for improving the efficiency of solar cells using brominated polycyclic thiophene. Background Art
[0002] Perovskite cells are solar cells that use perovskite-type organic metal halide semiconductors as light-absorbing materials. In recent years, perovskite solar cells have made rapid progress, with their efficiency increasing from 3.8% to more than 26%, attracting widespread attention. However, organic-inorganic hybrid perovskites have poor thermal stability due to their organic components, which hinders further commercial applications. Compared with organic-inorganic hybrid perovskites, cesium-based all-inorganic perovskites have excellent thermal stability and a suitable band gap of 1.7eV, making them ideal materials for preparing stacked solar cells.
[0003] As an important component of perovskite solar cells, the hole transport layer mainly collects and transports holes, while protecting the perovskite layer from oxygen and water vapor erosion, which plays an important role in the efficiency and stability of the cell. Currently, common hole transport materials include polytriarylamine (PTAA) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (C 81 H 68 N4O8, referred to as Spiro-OMeTAD), but they have significant disadvantages: first, the cost is high; second, due to low hole mobility and low conductivity, dopants need to be introduced. However, the introduced dopants, such as lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI), are hygroscopic and will cause phase transition and degradation of the perovskite layer. 13 N, abbreviated as tBP) will plasticize Spiro-OMeTAD, lower its glass transition temperature, and affect the thermal stability of the device. In order to avoid the above problems, poly (3-hexylthiophene-2,5-diyl) (P3HT) conductive conjugated polymer can be used as the hole transport layer, which has good conductivity and environmental stability and is easy to process. Summary of the invention
[0004] The present invention aims to provide a method for modifying P3HT with brominated polycyclic thiophene, which improves the transfer and extraction of charges in the hole transport layer by adjusting the orientation of P3HT and increasing the π-π stacking degree of P3HT, thereby achieving an improvement in the photoelectric conversion efficiency of perovskite solar cells.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for improving the efficiency of solar cells by using brominated polycyclic thiophene, wherein the perovskite layer material of the solar cell is CsPbI3, characterized in that an additive is added to a poly(3-hexylthiophene-2,5-diyl) (P3HT) solution to modify the P3HT, and the modified P3HT solution is spin-coated on the surface of the perovskite layer, wherein the additive is 2,5-bis(2-ethylhexyl)-3,6-di(thiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dihydropyrrolo[3,4-c]pyrrole-1,4-dihydropyrrolo[3,4-c]pyrrole-2,5-dihydropyrrolo[3,4-c]pyrrole-3 ... Ketone, 3-(5-bromo-2-thienyl)-2,5-bis(2-ethylhexyl)-2,5-dihydro-6-(2-thienyl)pyrrolo[3,4-c]pyrrole-1,4-dione or 3,6-bis(5-bromothien-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione. The above three additives are simply named 0-Br, 1-Br and 2-Br according to the total number of bromine atoms contained in each additive.
[0006] Furthermore, in the above-mentioned modified P3HT solution, the concentration of P3HT is 15 mg / mL, when the additive is 0-Br, the concentration of 0-Br added is 0.1~0.7 mg / mL, when the additive is 1-Br, the concentration of 1-Br added is 1.0~7.0 mg / mL, and when the additive is 2-Br, the concentration of 2-Br added is 0.5~2.0 mg / mL.
[0007] Further, preferably, in the modified P3HT solution, when the additive is 0-Br, the concentration of 0-Br is 0.5 mg / mL, when the additive is 1-Br, the concentration of 1-Br is 3.0 mg / mL, and when the additive is 2-Br, the concentration of 2-Br is 1.0 mg / mL.
[0008] Further, preferably, the additive is 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione, and the doping concentration is 1.0 mg / mL.
[0009] Furthermore, the three P3HT solutions with different additives were spin-coated at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, and then annealed on a heating stage at 100° C. for 3 minutes.
[0010] Among the additives used in the present invention, three additives have the same pyrrole structure, and the oxygen atom on the carbonyl group shows nucleophilicity, and the nucleophilicity of the three additives is the same. The α position on the original thiophene ring is electrophilic, and after it is replaced by the electron-withdrawing Br atom, the electron cloud density around the S atom is changed, so that this area is more likely to obtain electrons, showing stronger electrophilicity than the unsubstituted thiophene ring, and thus an adsorption effect different from that of P3HT is generated. This adsorption effect and interaction cause a greater π-π stacking degree between the additive and P3HT, and enhance the face-to-face orientation of P3HT. This orientation forms an interface between the perovskite and the P3HT film that is conducive to carrier transport, which will improve the carrier transport process and allow holes to move toward the positive electrode better.
[0011] Specifically, the method for preparing the additive-modified P3HT hole transport layer is characterized by comprising the following steps: (1) Preparation of precursor solution Additives were added to a P3HT solution with a concentration of 15 mg / mL, and the mixture was stirred evenly to form P3HT solutions modified with different additives, wherein the additives were 2,5-bis(2-ethylhexyl)-3,6-di(thien-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 0-Br), 3-(5-bromo-2-thienyl)-2,5-bis(2-ethylhexyl)-2,5-dihydro-6-(2-thienyl)pyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 1-Br), or 3,6-bis(5-bromothien-2-yl)-2,5-bis(2-ethylhexyl)-2,5 dihydropyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 2-Br). When the additive was 0-Br, the addition concentration was 0.1-0.7 mg / mL, when the additive is 1-Br, the added concentration is 1.0~7.0 mg / mL, when the additive is 2-Br, the added concentration is 0.5~2.0 mg / mL; (2) Deposition of P3HT hole transport layer modified with different additives The P3HT layer modified with different additives was deposited on the surface of the perovskite layer by spin coating, specifically, the spin coating was performed at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, and then annealed on a heating platform at 100°C for 3 minutes.
[0012] Most specifically, the method for preparing solar energy based on the above P3HT-based hole transport layer modified with different additives comprises the following steps: (1) Fluorine-doped tin oxide (FTO) conductive glass was cleaned with detergent, deionized water, isopropanol and ethanol in turn, each cleaning time was 40 min. After cleaning, the glass was blown dry with a nitrogen gun and cleaned with a UV ozone cleaner for 20 min. (2) Spin coating a 0.15M titanium n-butoxide solution on the FTO glass, specifically increasing the speed from 1000 rpm / s to 2000 rpm and spinning for 26 s. After spin coating, annealing was performed at 125 °C for 5 min, and then sintering was performed at 500 °C in a muffle furnace for 30 min to obtain a TiO2 electron transport layer. (3) Dissolve 0.8 mmol of dimethylamine lead iodide (DMAPbI3) and 0.8 mmol of cesium iodide (CsI) in 1 mL of dimethylformamide (DMF) to form a perovskite precursor solution. Spin-coat the prepared perovskite precursor solution on the electron transport layer by spin coating at 500 rpm for 5 s and then at 3000 rpm for 30 s. Then anneal at 210 °C for 4 min to obtain a CsPbI3 perovskite layer. (4) Prepare a P3HT solution with a concentration of 15 mg / mL, add additives to prepare a modified P3HT solution, spin-coat at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, spin-coat the modified P3HT solution on the surface of the CsPbI3 perovskite layer, and then anneal on a 100°C heating table for 3 minutes. In the modified P3HT solution, when the additive is 0-Br, the added concentration is 0.1~0.7 mg / mL, when the additive is 1-Br, the added concentration is 1.0~7.0 mg / mL, and when the additive is 2-Br, the added concentration is 0.5~2.0 mg / mL; (5) The device prepared in step (4) was placed in a mask plate and then transferred to a thermal evaporation film evaporator to deposit a 100 nm thick Ag metal electrode on the surface of the hole transport layer. The vacuum degree during deposition was 3.5×10 -4 Pa.
[0013] The present invention has the following technical effects: In the present invention, P3HT is modified by using additives. The additives interact with P3HT to improve the orientation and stacking degree of P3HT, making it easier for holes to be transferred to the hole transport layer, so that the device efficiency is increased from 14.70% (unmodified P3HT) to 16.16% (0-Br), 16.36% (1-Br), and 16.88% (2-Br), respectively, and the device performance is significantly improved. In addition, the additives used in the present invention have the advantages of low cost and solution processing, which can promote the commercialization process of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 : Chemical structural formulas of P3HT and three additives.
[0015] Figure 2 :a is an example of the additive and P3HT before adsorption; b is a schematic diagram of the interaction between P3HT and different additives and the adsorption energy (ΔE ads ).
[0016] Figure 3 : a is the one-dimensional intensity distribution diagram of the four films along the out-of-plane direction; b is the one-dimensional intensity distribution diagram of the four films along the in-plane direction.
[0017] Figure 4 : a is the current density-voltage diagram of the device with P3HT as the hole transport layer; b is the current density-voltage diagram of the device with P3HT:2-Br as the hole transport layer. DETAILED DESCRIPTION
[0018] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0019] Example 1 A method for preparing a solar cell based on an additive-modified P3HT hole transport layer comprises the following steps: (1) Fluorine-doped tin oxide (FTO) conductive glass was cleaned with detergent, deionized water, isopropanol and ethanol in turn, each time with solvent cleaning for 40 min. After cleaning, the glass was blown dry with a nitrogen gun and cleaned with a UV ozone cleaner for 20 min. (2) Spin coating a 0.15M titanium n-butoxide solution on the FTO glass, specifically increasing the speed from 1000 rpm / s to 2000 rpm and spinning for 26 s. After spin coating, annealing was performed at 125 °C for 5 min, and then sintering was performed at 500 °C in a muffle furnace for 30 min to obtain a TiO2 electron transport layer. (3) Dissolve 0.8 mmol of dimethylamine lead iodide (DMAPbI3) and 0.8 mmol of cesium iodide (CsI) in 1 mL of dimethylformamide (DMF) to form a perovskite precursor solution. Spin-coat the prepared perovskite precursor solution on the electron transport layer by spin coating at 500 rpm for 5 s and then at 3000 rpm for 30 s. Then anneal at 210 °C for 4 min to obtain a CsPbI3 perovskite layer. (4) Prepare a P3HT solution with a concentration of 15 mg / mL, add an additive to prepare a modified P3HT solution, spin-coat the modified P3HT solution on the surface of the CsPbI3 perovskite layer, spin-coat the solution on the surface of the CsPbI3 perovskite layer at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, and then anneal on a 100°C heating table for 3 minutes. In the modified P3HT solution, the additive is 2,5-bis(2-ethylhexyl)-3,6-di(thiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 0-Br), and the added concentration is 0.1~0.7 mg / mL, and a P3HT hole transport layer with different concentrations of 0-Br added is obtained, denoted as P3HT:0-Br; (5) The device prepared in step (4) was placed in a mask plate and then transferred to a thermal evaporation film evaporator to deposit a 100 nm thick Ag metal electrode on the surface of the hole transport layer. The vacuum degree during deposition was 3.5×10 -4 Pa.
[0020] According to the method of Example 1, the addition concentrations of the additive 0-Br were 0.0 mg / mL, 0.1 mg / mL, 0.3 mg / mL, 0.5 mg / mL and 0.7 mg / mL, respectively, and the photovoltaic parameters of the prepared perovskite solar cells are shown in Table 1.
[0021] Table 1: Photovoltaic parameters of perovskite solar cells with different 0-Br doping concentrations
[0022] It can be seen from the above table that by adding 0-Br to P3HT, the photoelectric conversion efficiency (PCE) is significantly improved, among which 0.5 mg / mL is the optimal addition concentration of 0-Br, at which the PCE improvement is most significant.
[0023] Example 2 A method for preparing a solar cell based on a P3HT hole transport layer modified with an additive comprises the following steps: (1) Fluorine-doped tin oxide (FTO) conductive glass was cleaned with detergent, deionized water, isopropanol and ethanol in turn, each time with solvent cleaning for 40 min. After cleaning, the glass was blown dry with a nitrogen gun and cleaned with a UV ozone cleaner for 20 min. (2) Spin coating a titanium n-butoxide solution with a concentration of 0.15 M on the FTO glass, specifically, increasing the speed from 1000 rpm / s to 2000 rpm and spin coating for 26 s, annealing at 125 °C for 5 min, and then annealing at 500 °C in air for 30 min to obtain a TiO2 electron transport layer; (3) Dissolve 0.8 mmol of dimethylamine lead iodide (DMAPbI3) and 0.8 mmol of cesium iodide (CsI) in 1 mL of dimethylformamide (DMF) to form a perovskite precursor solution. Spin-coat the prepared perovskite precursor solution on the electron transport layer by spin coating at 500 rpm for 5 s and then at 3000 rpm for 30 s. Then anneal at 210 °C for 4 min to obtain a CsPbI3 perovskite layer. (4) Prepare a P3HT solution with a concentration of 15 mg / mL, add an additive to prepare a modified P3HT solution, spin-coat the modified P3HT solution on the surface of the CsPbI3 perovskite layer, spin-coat the solution on the surface of the CsPbI3 perovskite layer at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, and then anneal on a 100°C heating table for 3 minutes. In the modified P3HT solution, when the additive is 3-(5-bromo-2-thienyl)-2,5-bis(2-ethylhexyl)-2,5-dihydro-6-(2-thienyl)pyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 1-Br), the added concentration range is 1.0~7.0 mg / mL, and a P3HT hole transport layer with different concentrations of 1-Br added is obtained, denoted as P3HT:1-Br; (5) The device prepared in step (4) was placed in a mask plate and then transferred to a thermal evaporation film evaporator to deposit a 100 nm thick Ag metal electrode on the surface of the hole transport layer. The vacuum degree during deposition was 3.5×10 -4 Pa.
[0024] According to the method of Example 2, the doping concentrations of the additive 1-Br were 0.0 mg / mL, 1.0 mg / mL, 3.0 mg / mL, 5.0 mg / mL and 7.0 mg / mL, respectively, and the photovoltaic parameters of the prepared perovskite solar cells are shown in Table 2.
[0025] Table 2: Photovoltaic parameters of perovskite solar cells with different 1-Br addition concentrations
[0026] It can be seen from the above table that by doping 1-Br in P3HT, the photoelectric conversion efficiency is significantly improved, among which 3.0 mg / mL is the optimal doping concentration of 1-Br, at which the photoelectric conversion efficiency is most significantly improved.
[0027] Example 3 A method for preparing solar energy based on an additive-modified P3HT-based hole transport layer comprises the following steps: (1) Fluorine-doped tin oxide (FTO) conductive glass was cleaned with detergent, deionized water, isopropanol and ethanol in turn, each time with solvent cleaning for 40 min. After cleaning, the glass was blown dry with a nitrogen gun and cleaned with a UV ozone cleaner for 20 min. (2) Spin coating a 0.15M titanium n-butoxide solution on the FTO glass, specifically increasing the speed from 1000 rpm / s to 2000 rpm and spinning for 26 s. After spin coating, annealing was performed at 125 °C for 5 min, and then sintering was performed in a muffle furnace at 500 °C for 30 min to obtain a TiO2 electron transport layer. (3) Dissolve 0.8 mmol of dimethylamine lead iodide (DMAPbI3) and 0.8 mmol of cesium iodide (CsI) in 1 mL of dimethylformamide (DMF) to form a perovskite precursor solution. Spin-coat the prepared perovskite precursor solution on the electron transport layer by spin coating. Spin at 500 rpm for 5 s, then at 3000 rpm for 30 s, and then anneal at 210 °C for 4 min to obtain a CsPbI3 perovskite layer. (4) Prepare a P3HT solution with a concentration of 15 mg / mL, add an additive to prepare an additive-modified P3HT solution, spin-coat the modified P3HT solution on the surface of the CsPbI3 perovskite layer, spin-coat the solution on the surface of the CsPbI3 perovskite layer at a speed of 2000 rpm / s and 4000 rpm for 26 seconds, and then anneal on a 100°C heating table for 3 minutes. In the modified P3HT solution, the additive is 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (denoted as 2-Br), and the added concentration range is 0.5~2.0 mg / mL, and a P3HT hole transport layer with different concentrations of 2-Br added is obtained, denoted as P3HT:2-Br; (5) The device prepared in step (4) was placed in a mask plate and then transferred to a thermal evaporation film evaporator to deposit a 100 nm thick Ag metal electrode on the surface of the hole transport layer. The vacuum degree during deposition was 3.5×10 -4 Pa.
[0028] According to the method of Example 3, the addition concentrations of the additive 2-Br were 0.0 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL and 2.0 mg / mL, respectively, and the photovoltaic parameters of the prepared perovskite solar cells are shown in Table 3.
[0029] Table 3: Photovoltaic parameters of perovskite solar cells with different 2-Br doping concentrations
[0030] It can be seen from the above table that the photoelectric conversion efficiency is significantly improved by adding 2-Br to P3HT, among which 1.0 mg / mL is the optimal doping concentration of 2-Br, at which the photoelectric conversion efficiency is most significantly improved.
[0031] The above embodiments are experiments conducted in batches. There are certain differences in the photovoltaic parameters corresponding to the undoped groups measured between the batches, but the differences are small and within the scope that can be understood in the art.
[0032] The chemical structural formulas of the three additives 0-Br, 1-Br and 2-Br and P3HT used in Examples 1, 2 and 3 are shown in Figure 1 As shown, the three additives have the same pyrrole structure, and the oxygen atom on the carbonyl group shows nucleophilicity, and the three additives have the same degree of nucleophilicity. The α position on the original thiophene ring is electrophilic. After it is replaced by the electron-withdrawing Br atom, the electron cloud density around the S atom is changed, making it easier for this area to obtain electrons, showing a stronger electrophilicity than the unsubstituted thiophene ring, and thus producing an adsorption effect different from that of P3HT. This adsorption and interaction results in a greater degree of π-π stacking between the additive and P3HT, and enhances the face-to-face orientation of P3HT. This orientation forms an interface between the perovskite and P3HT film that is conducive to carrier transport, which will improve the carrier transport process and allow holes to move better toward the positive electrode.
[0033] In order to clarify the difference between the number of bromine atoms on the additive and the electrophilicity and nucleophilicity of the additive, as well as the interaction between them and P3HT, the adsorption between P3HT and 0-Br, 1-Br, and 2-Br was calculated by density functional theory in the present invention. The schematic diagram of the additive and P3HT before adsorption is shown in Figure 2 a, The interaction between P3HT and additives is shown in Figure 2 b, calculated system of P3HT and three additives (E sys ) energy value and the adsorption energy ΔE of the two ads (ΔE ads =E sys – E P3HT -E additive ) See Table 4 (E P3HT 、E additive are the energy values of P3HT and additive molecules, respectively).
[0034] Table 4: P3HT (E P3HT ), additives (E additive ) and the molecular energy value of the system composed of P3HT and three additives (Esys ) energy value and the adsorption energy ΔE between the two ads
[0035] From the data in Table 4 above, we can see that the adsorption energy between each additive and P3HT is different. The adsorption energy generated by the reaction between 0-Br and P3HT is -0.05eV, the adsorption energy generated by the reaction between 1-Br and P3HT is -0.07eV, and the adsorption energy generated by the reaction between 2-Br and P3HT is -6.56eV. Since the adsorption energies are all negative, it shows that these three additives have adsorption effects on P3HT and the adsorption effect between 2-Br and P3HT is much stronger than that between 0-Br and 1-Br (the larger the absolute value of the adsorption energy, the greater the adsorption energy and the more stable the structure).
[0036] Subsequently, GIWAXS characterization was performed ( Figure 3 ), the results show that the out-of-plane (1 0 0), (2 0 0), and (3 00) diffraction rings q z = 0.385, 0.725, 1.08 Å -1 The out-of-plane (1 0 0), (20 0), and (3 0 0) diffraction rings of P3HT:0-Br, P3HT:1-Br, and P3HT:2-Br are all at q z =0.375, 0.720, 1.085Å -1 That is, the position of the external diffraction ring after addition is consistent with that before addition, which shows that the three additives have not changed the "edge-on" configuration of P3HT. The in-plane (0 1 0) diffraction rings of P3HT, P3HT:0-Br, P3HT:1-Br, and P3HT:2-Br are located at q xy =1.50, 1.50, 1.55, 1.54Å -1 At , the corresponding π-π stacking distances are 4.19, 4.19, 4.06, and 4.08 Å, respectively. For the out-of-plane and in-plane diffraction intensities, from Figure 3 a and its corresponding illustration, we can see that the out-of-plane diffraction intensity of the film is weakened after adding the additive. Figure 3b It can be seen that the in-plane diffraction intensity of the film is enhanced after the addition of additives. The intensity of the out-of-plane diffraction is weakened and the intensity of the in-plane diffraction is enhanced, indicating that the addition of the modifier improves the face-to-face stacking orientation of P3HT, that is, the "face-on" configuration, which means that more thiophene groups are laid flat on the perovskite, which is more conducive to the transport of carriers between the perovskite and the hole transport layer. Next, with the device structure of FTO / TiO2 / CsPbI3 / P3HT (unmodified or modified with additives) / Ag, four types of solar cells were prepared with unadded P3HT, P3HT:0-Br with a 0-Br addition concentration of 0.5 mg / mL, P3HT:1-Br with a 1-Br addition concentration of 3.0 mg / mL, and P3HT:2-Br with a 2-Br addition concentration of 1.0 mg / mL as the hole transport layer. The number of each of the four devices is 20, and the statistical results of photovoltaic parameters are shown in Table 5.
[0037] Table 5: Statistical results of photovoltaic parameters of four types of solar cells
[0038] As can be seen from the table above, the photoelectric conversion efficiency (PCE) of the device without additives (P3HT) is 14.7%, and the open circuit voltage (Voc) of the devices with additives (P3HT:0-Br, P3HT:1-Br and P3HT:2-Br) is increased from 1.01V to 1.05V, and the short circuit current density (J SC ) also improved to a certain extent, and the fill factor (FF) increased from 71.52% of the physical additive to 76.39% (0-Br), 76.65% (1-Br) and 76.27% (2-Br). Finally, the device efficiency increased to 16.16% (0-Br), 16.36% (1-Br) and 16.88% (2-Br) (average PCE). The current density-voltage (JV) curves of solar cells (champion cells) based on P3HT and P3HT:2-Br as hole transport layers are shown in the figure. Figure 4 shown.
Claims
1. A method for improving the efficiency of solar cells by using brominated polycyclic thiophene, wherein the perovskite layer material of the solar cell is CsPbI3, characterized in that: Additives are added to a poly (3-hexylthiophene-2,5-diyl) (P3HT) solution to prepare a modified P3HT solution, and the modified P3HT solution is spin-coated on the surface of the perovskite layer to prepare a hole transport layer. The additives used in the modified P3HT solution are 2,5-bis (2-ethylhexyl) -3,6-di (thiophene-2-yl) -2,5-dihydropyrrolo [3,4-c] pyrrole-1,4-dione, 3- (5-bromo-2- In the above three additives, 0-Br, 1-Br and 2-Br are simply named according to the total number of bromine atoms contained in each additive, 2,5-bis(2-ethylhexyl)-2,5-dihydro-6-(2-thienyl)pyrrolo[3,4-c]pyrrole-1,4-dione or 3,6-bis(5-bromothien-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.
2. The method for improving the efficiency of solar cells by using brominated polycyclic thiophene as claimed in claim 1, characterized in that: In the modified P3HT solution, the concentration of P3HT is 15 mg / mL, the added concentration of 0-Br is 0.1~0.7 mg / mL, the added concentration of 1-Br is 1.0~7.0 mg / mL, and the added concentration of 2-Br is 0.5~2.0 mg / mL.
3. A method for improving the efficiency of solar cells using brominated polycyclic thiophenes according to claim 1 or 2, characterized in that: The concentration of 0-Br added was 0.5 mg / mL, the concentration of 1-Br added was 3.0 mg / mL, and the concentration of 2-Br added was 1.0 mg / mL.
4. A method for improving the efficiency of solar cells using brominated polycyclic thiophenes according to any one of claims 1 to 3, characterized in that: The modified P3HT solution was deposited on the prepared perovskite film by spin coating, with a speed of 2000 rpm / s, a spin coating speed of 4000 rpm, and a spin coating time of 26 s, and then annealed on a heating table at 100°C for 3 min.
5. A method for preparing a solar cell based on a modified P3HT-based hole transport layer, characterized in that: The steps include: (1) Fluorine-doped tin oxide (FTO) conductive glass was cleaned with detergent, deionized water, isopropanol and ethanol in turn, each cleaning lasting 40 min. The cleaned glass was blown dry with a nitrogen gun and cleaned with a UV-ozone cleaner for 20 min. (2) Spin coating a 0.15M titanium n-butoxide solution on the FTO glass, specifically increasing the speed from 1000 rpm / s to 2000 rpm and spinning for 26 s. After spin coating, annealing was performed at 125 °C for 5 min, and then sintering was performed at 500 °C in a muffle furnace for 30 min to obtain a dense TiO2 electron transport layer. (3) Dissolve 0.8 mmol of dimethylamine lead iodide (DMAPbI3) and 0.8 mmol of cesium iodide (CsI) in 1 mL of dimethylformamide (DMF) to form a perovskite precursor solution. Spin-coat the perovskite precursor solution on the TiO2 electron transport layer by spin coating at 500 rpm for 5 s and then at 3000 rpm for 30 s. Then anneal at 210 °C for 4 min to obtain a CsPbI3 perovskite layer. (4) preparing a P3HT solution with a concentration of 15 mg / mL, adding an additive to prepare a modified P3HT solution, and spin-coating the modified P3HT solution on the surface of the CsPbI3 perovskite layer at a speed of 2000 rpm / s, a rotation number of 4000 rpm, and a spin coating time of 26 s, and then annealing on a 100°C heating table for 3 min. In the modified P3HT solution, when the additive is 0-Br, the additive concentration is 0.1-0.7 mg / mL, when the additive is 1-Br, the additive concentration is 1.0-7.0 mg / mL, and when the additive is 2-Br, the additive concentration is 0.5-2.0 mg / mL; (5) The device prepared in step (4) was placed in a mask plate and then transferred to a thermal evaporation film evaporator. A 100 nm thick Ag metal electrode was deposited on the surface of the hole transport layer by thermal evaporation. The vacuum degree during deposition was 3.5×10 -4 Pa.